Information technology. International standardized profiles AFTnn. File transfer, access and management. AFT11. Simple file transfer service (unstructured) (regional variant of ISO/IEC ISP 10607-3:1995) Part 3, (15th March 1997) - British Standards Institution,
No abstract available